Surfactants as Performance-Enhancing Additives in Supercapacitor Electrolyte Solutions—An Overview - Xuecheng Chen; Rudolf Holze (Batteries, 2023)
Wetting the surface area of an electrode material as completely as possible is desirable to achieve optimum specific capacity of an electrode material. Keeping this surface area utilized even at high current densities and even when inside pores is required for high capacitance retention. The addition of surfactants at very small concentrations to aqueous supercapacitor electrolyte solutions has been suggested as a way to improve performance in terms of capacitance, capacitance retention at increased current density and stability. Effects are pronounced with carbon materials used in electrochemical double-layer capacitors; they are also observed with redox materials. The causes of the observed improvements and mode of operation of the added surfactants seem to need further investigation; they are inconclusive beyond the obvious statement of increased wetting. Reported examples and the current state of understanding are reviewed.